Advances in Dermatological Sciences 2013
DOI: 10.1039/9781849734639-00157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat on Diclofenac Permeation Through Human Skin

Abstract: The application of thermal energy to enhance the percutaneous absorption of drugs offers an encouraging prospect for overcoming the skin barrier. External membranes such as the skin present a considerable barrier to the permeation of drugs, limiting the types of treatment that can be given via this route. These barrier properties are mostly dependent on the stratum corneum (SC), the outermost layer of skin, which in most cases is known to be the rate limiting step for drug diffusion across the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In agricultural settings where significant seasonal temperature fluctuations are commonly experienced, this may influence the performance of the protective material. Pharmaceutical studies have shown the application of heat increases transdermal penetration as a result of increased diffusion and intercellular mass flow [21,22,23]. A comparable effect on chemical protective gloves might occur due to increased diffusion and solubility.…”
Section: Introductionmentioning
confidence: 99%
“…In agricultural settings where significant seasonal temperature fluctuations are commonly experienced, this may influence the performance of the protective material. Pharmaceutical studies have shown the application of heat increases transdermal penetration as a result of increased diffusion and intercellular mass flow [21,22,23]. A comparable effect on chemical protective gloves might occur due to increased diffusion and solubility.…”
Section: Introductionmentioning
confidence: 99%